Representation of Reading Literacy Elements in the Curricula of First- and Second-Cycle Study Programmes in Primary and Preschool Education - Šek, Polonca; Ivanuš Grmek, Milena (Bralni vzori 2, 2025)
The paper presents the results of an analysis of the study programmes Preschool Education and Primary Education from the perspective of reading literacy. Elements of reading literacy are not present in all of the analysed course units. They appear most frequently in units related to youth literature and language education (both Slovene and English). The most prominent are the first component (speaking) and the fifth component of reading literacy (vocabulary). The latter is a key component in academic study, as it involves the acquisition and expansion of vocabulary necessary for successful reading comprehension, learning, and communication. It also includes understanding word meanings and using them in both receptive and productive language tasks, as well as the use of linguistic resources and reference tools. The components text comprehension and text production are also substantially represented. The component critical reading is significantly more present at the second cycle of study, where students are expected not only to understand texts but also to engage in critical thinking, evaluation, and forming their own perspectives on what they have read.